The Employer Branding of Cultural Heritage Hotel’s Impact on Electronic Word of Mouth - Harimurti, Wibisono; Rufaidah, Popy (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the effect of employer branding on electronic word of mouth in one of the cultural heritage hotels. Data were collected through a survey distributed to 121 employees population of one of the hotels in Bandung. In this study, the independent variable employer branding uses four dimensions, namely work culture, salary and incentives, diversity and ethics, and CSR. As for the dependent variable electronic word of mouth, the dimensions used are volume and valance. These dimensions were adopted from previous studies that used employer branding and electronic word of mouth as the main focus of research. Hypothesis testing, validity, and reliability were tested using PLS-SEM as the analysis method. The research results that have been stated, show that employer branding affects electronic word of mouth in employees and the effect of employer branding on electronic word of mouth is positive and significant.